Absence: Adoption in Art - Greenway, Kate (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
While the prolific ‘Madonna and child’ painterly motif, and recent MIRCI publicationsattest to the existence of representations of mothering in fine art throughthe ages, as well as contemporary art and photography, notably absent are images ofa different kind of maternity, and non-normative family formation unreliant onbiogenetic kinship or childbirth: the adoptive experience. Cover art for publications,usually from small press, or children’s book illustrations, saccharine posters and calligraphicproclamations available on the Internet appear to form this canon. Whataccounts for the historical absence of true artistic depictions of the social, cultural,psychological, physiological, and political complexity of adoption? What does theprivileging of the ‘biological imperative’ communicate? Finding art and artists whorepresent the adoptee, birthmother or adoptive mother was a challenge I took up, asa member of the adoption triad, familiar with some of its lingering pressures andstigmas despite growing openness in definitions of family and motherhood. Leadingto slim offerings of multimedia, installation art, and limited edition artist’s books,of the few contemporary images that do exist, I investigate what happens whenwe deconstruct them.